Family cohesion and psychopathological symptoms in pediatric obesity: Is there an indirect effect?. Issue 1 (2nd January 2018) - Frontini, Roberta; Canavarro, Maria Cristina; Moreira, Helena
ABSTRACT: The prevalence of pediatric obesity is increasing worldwide, which is particularly concerning given its negative impact on adjustment (e.g., quality of life, psychopathological symptoms) and physical health (e.g., high blood pressure, cardiovascular problems). It is important to understand the factors that may improve children's/adolescents' adjustment to overweight/obesity. This study aims to assess the indirect effect of family cohesion on children's/adolescents' internalizing/externalizing symptoms through body esteem and social life. The sample comprises 182 treatment-seeking children/adolescents with overweight/obesity and their mothers. Mothers completed a measure of family cohesion (Family Environment Scale), and children/adolescents completed measures of body esteem, social life (Impact of Weight on Quality of Life-Kids), and internalizing/externalizing symptoms (Strengths and Difficulties Questionnaire). Path analyses indicated a significant indirect effect between family cohesion and internalizing symptoms through children's/adolescents' body esteem and social life. Higher levels of family cohesion were linked to higher levels of body esteem, which were linked to higher levels of social life that, in turn, were associated with lower levels of internalizing symptoms. The results suggest the importance of body esteem and social life in explaining the link between family cohesion and children's/adolescents' internalizing symptoms. The results also suggest that belonging to a more cohesive family may improve the mental health of children/adolescents with overweight/obesity.